A doxorrubicina e o paclitaxel, usados na quimioterapia neoadjuvante para câncer de mama, ativam receptores toll-like e proteínas de sua sinalização, PI3K e Akt - Quispe, Celia Choquenaira (2023)
Introduction: Breast cancer is the most prevalent type of cancer among women worldwide. Neoadjuvant chemotherapy (QTneo) based on Doxorubicin (DOX)/Cyclophosphamide and Paclitaxel (PTX) aims to reduce tumor size and improve overall survival. The cell damage caused by DOX releases mitochondrial DNA, a TLR9 ligand. PTX has also been described as a TLR4 agonist. However, whether DOX or PTX act by modulating the TLR/PI3K/AKT pathway. Objective: To evaluate whether doxorubicin and paclitaxel, used in neoadjuvant chemotherapy for breast cancer, activate toll-like receptors and their signaling proteins, PI3K and AKT. Methodology: Surgical specimens from patients with breast cancer after QTneo were evaluated for the expression of TLR4 and TLR9. In vitro, MCF-7 and MDA-MB-231 tumor cells were divided into control (DMEN) and groups treated for 24h with lipopolysaccharide (LPS 10μg/ml in MDA-MB-231; 20μg/ml in MCF-7); CpG- oligodeoxynucleotides (CpG-ODN 10μg/ml), DOX (0.3μM/MDA-MB-231; 0.1μM/MCF-7) or PTX (5nM/MDA-MB-231; 5μM/MCF-7). The expression of Il-33, Il-18, Il-1β and Il-6 (qPCR) and TLR4, TLR9, PIK3δ, PI3Kγ and p-AKT were quantified by flow cytometry (FC) and immunofluorescence (IF). The adipocytes (HAd) were divided into control (DMEN), HAd/DOX (DOX:0.1μM or 0.3μM) and HAd/PTX (PTX:5μM or 5nM). The supernatant was used to treat the tumor cells and to measure adipocytokines. Silenced MCF-7 cells (siRNA- TLR4) were treated with the chemotherapeutic agents and the expression of TLR4, AKT and pAKT was evaluated by Western Blotting (WB). Results: Tumors from patients expressed TLR4. In MDA-MB-231 cells, we observed the expression of TLR4:25%(LPS), 67%(DOX) and 40%(PTX); TLR9:34%(CpG-ODN), 58%(DOX) and 31%(PTX). Additionally, LPS, CpG-ODN, DOX and PTX increased the expression of PIK3δ:24%,27%,57% and 66%, PI3Kγ:33%, 36%,100% and 52%; and p-AKT:37%,45%,176% and 93% respectively. Similarly, MCF-7 cells showed expression of TLR4:66%(LPS), 109%(DOX) and 62%(PTX); TLR9:15%(CpG-ODN), 53%(DOX) and 47%(PTX); PIK3δ:40%,29%,67% and 79%; PI3Kγ:31%,19%,113% and 136%; and p-AKT:53%,49%,123% and 170% respectively. Furthermore, cytokine expression was observed in MCF-7 (PTX: Il-6, Il-33, Il-18 and Il-1β; DOX: Il-18) and MDA-MB-231 (PTX: Il-6 and Il-33; DOX: Il-6). In HAd stimulated with the chemotherapy drugs, an increase in leptin was observed. MDA-MB-231 cells treated with the HAd/DOX or HAd/PTX supernatant respectively increased the expression of TLR4:89%, 3%; TLR9:75%, 7%; of PIK3δ:90% and 0%, PI3Kγ: 68% and 58%; and p-AKT: 90% and 25%. Similarly, MCF-7 cells treated with HAd/DOX or HAd/PTX respectively increased the expression of TLR4:30% and 34%; TLR9:69% and 81%; PIK3δ:53% and 33%; PI3Kγ:94% and 72%; and p-AKT:83% and 35%. MCF-7 silenced and treated with the chemotherapy drugs showed a decreased expression of TLR4. Conclusion: DOX and PTX increased the expression of TLR4, TLR9, PI3Kδ, PI3Kγ, pAKT, Il-33, Il-18, Il-1β and Il-6 in cells. The HAd/DOX and HAd/PTX supernatant increased the expression of TLR4, TLR9, PI3Kδ, PI3Kγ and p-AKT. This action was probably mediated by the leptin released by the adipocytes.